Estrategia metodológica para estimular el desarrollo del pensamiento lógico matemático en los estudiantes de cuarto grado de la Unidad Educativa. “Emigdio Esparza Moreno” de la ciudad de Babahoyo, provincia de los Ríos. - Herrera Alegria, Karen Dayana (2018)
The present thesis project aims to contribute in the process innovation of ensenanza_ that allows the child an integral development, but in particular strengthen loas skills for learning and development of logical thinking mathematician. The mathematical logical development is the fruit earlier, safer and more objective of the human mentality; It is for them the importance that requires study, reflection and analysis of this subject. Throughout time mathematics has used various objectives, a study of good performance in mathematics is also associated, a capable person, with broad prospects for professional development. But for ordinary students mathematics is still a subject that is complex, with a cryptic language and of little significance in their daily lives. The importance of mathematics lies in that offers a set of procedures of analysis, modeling, calculation, measurement and estimation of the natural and social world of mathematics as a subject taught in school institutions in the basic level, should be become part of the integral formation of the human being. In practice, logical mathematical procedures are always linked to a specific content that depends on the scope of application and that adds a specific component, in a close relationship with the general component. Although there is a close link between these two components, they are relatively independent, which are expressed in the possibility of the individual which dominates the procedure, apply the logical part to any specific content. Logical procedures do not depend on the specific content, while specific procedures can be used only in a certain area. On the other hand, in the real activity of man, logical procedures always run with some specific content. The following work focuses on using methodological strategies for stimulating the development of mathematical logic thinking in fourth-graders, whose purpose is to propose the comprehensive participation of the child/children as an essential part. For this reason it is necessary to apply active methodological strategies, through which it acquires habits and skills should be encouraged on the development of comprehension and written expression - using these skills children can develop and be able of solve problems in their daily activities.